Elaboração e validação de vídeo educativo para adesão de mulheres com prolapso de órgãos pélvicos ao uso de pessário vaginal - Bezerra, Karine de Castro (2016)
The study aimed to develop and validate an educational video to promote the accession of women with pelvic organ prolapse the use of vaginal pessary. It was a methodological research. To conduct the study, were followed two phases: development and validation of the video. In constructing the video were followed three phases: pre-production (synopsis, argument, script, storyboard), production and post-production. For the construction of the proposed educational material, it was first identified target group profile to be established content and the language of video. During this phase, the researcher followed by 12 months the pessary of consultation, and accompanied 17 women. It was identified that the main difficulties women about the treatment pessary passed by the field of knowledge, hence they did not adhere to treatment or interrupted after accepting insert the device. For the appearance of validation, content and script technical and educational video, we selected 24 judges according to pre-established criteria, 12 health and 12 of the communication area, and for the appearance of validation by the relevant public were selected 22 women, captured in the General Hospital of Fortaleza, located in the city of Fortaleza, Ceará. The data collection period with judges and women occurred between January 2014 and November 2015. For data collection, three instruments were used, two targeted judges, respectively content and appearance, and the other to the target audience. The validity of video content, the Content Validity Index (CVI) has been used, with cutoff of 0.80. The validity of appearance by the judges and audience were considered validated the items you obtain a minimum level of agreement of 75% in positive responses. The suggestions and opinions were compiled and presented in tables. The educational video study was the first to be developed within the theme on the national scene, being a material considered valid from the point of view of appearance and content, as presented good overall IVC (0.991) from the validation by judges and level excellent agreement between the judges (91.1% -100%) and representatives of the target audience (96% to 100%). Thus, it consists of a technology that should be considered in the context of educational activities as a tool to encourage adherence to conservative treatment with vaginal delivery in women with indication of this therapeutic approach. In the face of suggestions and contributions from the validation process, even reaching favorable IVC, the educational video has undergone modifications, adjustments and additions to make it more effective, changing from 7 minutes to 10 minutes in the final version.